Enhancing The Accuracy And Effectiveness Of Radiological Techniques In Detecting Late-Stage Hip Joint Complications Following Covid-19 Infection - Ablyazov A.A (Zien Journals, 2025)
The objective of this study is to improve the diagnostic effectiveness of radiological methods in identifying late-stage post-COVID pathologies of the hip joint. This includes defining specific radiological features and patterns that characterize these complications, thereby aiding in early detection, accurate staging, and appropriate management of post-COVID hip joint diseases. Timely and precise diagnosis is essential to prevent progression to severe joint damage and reduce the risk of disability
Keywords: essential; progression; diagnosis